Cues to deception: can complications, common knowledge details, and self-handicapping strategies discriminate between truths, embedded lies and outright lies in an Italian-speaking sample? - Caso, Letizia; Cavagnis, Lucrezia; Vrij, Aldert; Palena, Nicola (Frontiers in Psychology, 2023)
Deception research has shown that analysing verbal content can be effective to distinguish between truths and lies. However, most verbal cues are cues to truthfulness (truth tellers report the cue more than lie tellers), whereas cues to deception (lie tellers report the cue more than truth tellers) are largely absent. The complication approach, measuring complications (cue to truthfulness), common knowledge details (cue to deception), self-handicapping strategies (cue to deception), and the ratio of complications, aims to fill this gap in the literature. The present experiment examined the effectiveness of the complication approach when varying the amount of lying, with an Italian sample. Seventy-eight participants were assigned to one of three different experimental conditions: Truth tellers (telling the truth about the event), embedders (providing a mixture of truthful and false information) and outright lie tellers (providing false information). Participants were interviewed about a past experience concerning an out of the ordinary event. Complications discriminated truth tellers from lie tellers. The absence of significant effects for common knowledge details and self-handicapping strategies, the limitations of the experiment and suggestions for future research are discussed.